Footfall energy harvesting : footfall energy harvesting conversion mechanisms - Balouchi, Farouk (2013)
Ubiquitous computing and pervasive networks are prevailing to impact almost every part of our daily lives. Convergence of technologies has allowed electronic devices to become untethered. Cutting of the power-cord and communications link has provided many benefits, mobility and convenience being the most advantageous, however, an important but lagging technology in this vision is the power source. The trend in power density of batteries has not tracked the advancements in electronic systems development. This has provided opportunity for a bridging technology which uses a more integrated approach with the power source to emerge, where a device has an onboard self sustaining energy supply. This approach promises to close the gap between the increased miniaturisation of electronics systems and the physically constrained battery technology by tapping into the ambient energy available in the surrounding location of an application. Energy harvesting allows some of the costly maintenance and environmentally damaging issues of battery powered systems to be reduced. This work considers the characteristics and energy requirements of wireless sensor and actuator networks. It outlines a range of sources from which the energy can be extracted and then considers the conversion methods which could be employed in such schemes. This research looks at the methods and techniques for harvesting/scavenging energy from ambient sources, in particular from the motion of human traffic on raised flooring and stairwells for the purpose of powering wireless sensor and actuator networks. Mechanisms for the conversion of mechanical energy to electrical energy are evaluated for their benefits in footfall harvesting, from which, two conversion mechanisms are chosen for prototyping. The thesis presents two stair-mounted generator designs. Conversion that extends the intermittent pulses of energy in footfall is shown to be the beneficial. A flyback generator is designed which converts the linear motion of footfall to rotational torque is presented. Secondly, a cantilever design which converts the linear motion to vibration is shown. Both designs are mathematically modelled and the behaviour validated with experimental results & analysis. Power, energy and efficiency characteristics for both mechanisms are compared. Cost of manufacture and reliability are also discussed.
HydraID: hull:8433 Hydra Discover Access Group: public ETD Collection: ETDEngineering
Keywords: Engineering